RITMO, POESIA E MATEMÁTICA - Os caminhos percorridos no desenrolar da nossa pesquisaRHYTHM, POETRY AND MATHEMATICS – The Paths Crossed in the Course of our Research (PerCursos, 2010)
O presente artigo tem como objetivo propor a inserção de conteúdos trabalhados de forma não-linear, interdisciplinar e criativa em aulas de matemática, através de poemas e canções em língua portuguesa. O uso lúdico da palavra escrita revela-se eficaz na construção de propostas de problemas matemáticos, e tanto a palavra quanto sua simbologia surgem potencializadas sob o influxo da linguagem poética. Rimar e calcular mostra-se possível e educativo, além de representar uma alternativa divertida em salas de aula dos professores de Matemática e/ou de Língua Portuguesa. A presente pesquisa reflete também sobre a importância da transposição didática criativa dos conteúdos de matemática na escola fundamental e enfatiza a necessidade da instrumentação dos professores para a construção desses conhecimentos de forma inovadora e integrada à vida cotidiana dos estudantes. Palavras-Chave: Linguagem. Poesia. Matemática. Abstract The present work aims at proposing the inclusion of contents that were worked in a non-linear, creative and interdisciplinary way in Math classes, by means of poems and songs in Portuguese language. The playful use of the written word proves to be efficient in the building propositions of Math problems, and both the word and its symbology appear to become more powerful under the influx of the poetic language. To rime and to calculate show to be both possible and educational, in addition to representing a fun alternative in Math and Portuguese Language classes. The present research also reflects the significance of the creative didactic transposition of Math contents in Elementary Schools, as well as it stresses the need of preparing those teachers in the building of such knowledges in an innovative way and integrated to the students’ every day lives. Keywords: Language. Poetry. Math.